Foodborne Toxicity in the Pediatric Population: Etiology, Diagnosis, and Prevention Strategies - Ferizat Dika-Haxhirexha; Aferdita Ademi; Aulona Haxhirexha; Sevdije Koxha; Shqiponja Turkeshi (Albanian Journal of Trauma and Emergency Surgery)
Introduction: Foodborne intoxications persist as a significant and urgent public health concern globally, impacting both developing and developed nations. The incidence, particularly among children, escalates notably during the summer months, underscoring the severity of the issue.